الأبعاد الفنية والموضوعاتية في القصة القصيرة جدا "قراءة في حاء الحرية سعيد الريحاني نماذج مختارة" - كريم حريقة (My University, 2026)
Abstract: This study examines the artistic and thematic dimensions of the very short story through a reading of the collection "Haa' of Freedom" by the Moroccan writer Said Rihani. This collection is considered a modern narrative model that has contributed to establishing this literary genre and highlighting its artistic and semantic characteristics. The study aims to reveal the most prominent narrative components and artistic techniques employed in the very short story, and to analyze the thematic dimensions addressed by the writer, while also highlighting the relationship between the title and the stories and its role in generating meaning. The study adopts a descriptive-analytical approach based on reading and analyzing selected texts both artistically and thematically. It is divided into two chapters. The first chapter is dedicated to the theoretical and conceptual framework of the very short story, including its definition, origins, artistic characteristics, techniques, and key figures. The second chapter presents an applied study of the artistic and thematic dimensions in selected examples from the collection "Haa' of Freedom." The study concluded that Saeed Al-Rihani employed a range of modern narrative techniques suited to the nature of the very short story, such as brevity, condensation, irony, suggestion, and symbolism. He also addressed numerous human, social, and intellectual issues related to freedom, social reality, and the constraints imposed on the individual. The study demonstrated that the title represents a fundamental semantic element that contributes to constructing meaning and guiding the reader's reception, reflecting the richness and distinctiveness of the writer's narrative experience within the realm of the very short story. ------------------------ الملخص: تناولت هذه الدراسة موضوع الأبعاد الفنية والموضوعاتية في القصة القصيرة جدا، من خلال قراءة في مجموعة "حاء الحرية" للكاتب المغربي سعيد الريحاني، باعتبارهمن النماذج السردية الحديثة التي أسهمت في ترسيخ هذا الجنس الأدبي وإبراز خصوصياته الفنية والدلالية. وهدفت الدراسة إلى الكشف عن أبرز المكونات السردية والتقنيات الفنية المعتمدة في القصة القصيرة جداً، وتحليل الأبعاد الموضوعاتية التي عالجها الكاتب، مع إبراز العلاقة بين العنوان والنصوص القصصية ودوره في إنتاج الدلالة. واعتمدت الدراسة على المنهج الوصفي التحليلي القائم على قراءة النصوص المختارة وتحليلها فنياً وموضوعاتياً، وقد تم تقسيم الدراسة إلى فصلين؛ خصص الفصل الأول للإطار النظري والمفاهيمي للقصة القصيرة جداً من حيث مفهومها، نشأتها، خصائصها الفنية، تقنياتها وأهم روادها، بينما تناول الفصل الثاني الدراسة التطبيقية للأبعاد الفنية والموضوعاتية في نماذج مختارة من مجموعة "حاء الحرية". وتوصلت الدراسة إلى أن سعيد الريحاني وظّف مجموعة من التقنيات السردية الحديثة التي تتلاءم مع طبيعة القصة القصيرة جداً، كالاختزال والتكثيف والمفارقة والإيحاء والرمزية، كما عالج العديد من القضايا الإنسانية والاجتماعية والفكرية المرتبطة بالحرية والواقع الاجتماعي والقيود المفروضة على الفرد، وأثبتت الدراسة أن العنوان يمثل عنصراً دلالياً أساسياً يسهم في بناء المعنى وتوجيه عملية التلقي، مما يعكس ثراء التجربة السردية للكاتب وتميزها داخل فضاء القصة القصيرة جدا. --------------- Résumé : Cette étude examine les dimensions artistiques et thématiques de la nouvelle très courte à travers une lecture du recueil « Haa' de la Liberté » de l'écrivain marocain Saïd Rihani. Ce recueil est considéré comme un modèle narratif moderne ayant contribué à l'établissement de ce genre littéraire et à la mise en lumière de ses caractéristiques artistiques et sémantiques. L'étude vise à révéler les composantes narratives et les techniques artistiques les plus marquantes employées dans la nouvelle très courte, et à analyser les dimensions thématiques abordées par l'auteur, tout en soulignant la relation entre le titre et les nouvelles et son rôle dans la construction du sens. L'étude adopte une approche descriptive et analytique fondée sur la lecture et l'analyse, tant artistique que thématique, d'une sélection de textes. Elle se divise en deux chapitres. Le premier chapitre est consacré au cadre théorique et conceptuel de la nouvelle très courte, incluant sa définition, ses origines, ses caractéristiques artistiques, ses techniques et ses figures clés. Le second chapitre présente une étude appliquée des dimensions artistiques et thématiques à travers des exemples choisis du recueil « Haa' de la Liberté ». L'étude conclut que Saeed Al-Rihani a employé un éventail de techniques narratives modernes adaptées à la nature de la nouvelle très courte, telles que la brièveté, la condensation, l'ironie, la suggestion et le symbolisme. Il a également abordé de nombreuses questions humaines, sociales et intellectuelles liées à la liberté, à la réalité sociale et aux contraintes imposées à l'individu, L'étude démontre que le titre constitue un élément sémantique fondamental qui contribue à la construction du sens et oriente la réception du lecteur, reflétant la richesse et la singularité de l'expérience narrative de l'auteur dans le domaine de la nouvelle très courte.
Keywords: Artistic and thematic dimensions; short story; freedom; Saeed Al-Rihani.; الابعاد الفنية والموضوعاتية، القصة القصيرة، حاء الحرية، سعيد الريحاني; Dimensions artistiques et thématiques; nouvelle; liberté